2019
DOI: 10.1055/s-0040-1701145
|View full text |Cite
|
Sign up to set email alerts
|

Arch Length and Palatal Rugae: An Adjunct in Gender Discrimination

Abstract: Introduction Palatal rugae or plica palatine are the finger prints of the oral cavity and the arch length varies between males and females. These two parameters constitute an integral part of the anthropometric studies in the realms of dentistry as well as forensic odontology. The aim of this study was to assess whether any relationship existed between the upper arch length and the rugae pattern and whether these two parameters showed any gender differentiation. Materials and Methods The sample consisted of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
2
Order By: Relevance
“…Our study did not reveal a significant difference with regard to gender, which is contradictory to literature where a moderate discrimination with respect to gender has been identified in the number, length, size and direction of the rugae [ 11 – 26 ]. However, the studies did not take into account the posterior extension.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study did not reveal a significant difference with regard to gender, which is contradictory to literature where a moderate discrimination with respect to gender has been identified in the number, length, size and direction of the rugae [ 11 – 26 ]. However, the studies did not take into account the posterior extension.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the literature suggesting moderate gender differences in the number, length, size, and direction of rugae, the current study found no significant correlation concerning gender [28,45]. However, the studies did not account for the posterior extension of palatal rugae.…”
Section: Discussioncontrasting
confidence: 99%
“…When rugae patterns of both the groups were compared, the results were found to be statistically significant p < 0.05. 16 , and circular (0.03 ± 0.17) patterns. There were no statistically significant differences in the wavy, curve, and circular shape of palatal rugae between males and females.…”
Section: Discussionmentioning
confidence: 93%